Beauty regimes a history of power and modern empire in the Philippines, 1898-1941 - Clutario, Genevieve Alva 1981- (Duke University Press, 2023)
"In Beauty Regimes, Genevieve Clutario reveals how beauty politics in the Philippines created new relationships between colonial institutions, private industries, and diverse social worlds. During the turbulent transition between Spanish, US, and Japanese empires and the anti-colonial nationalist movement in the Philippines, beauty and fashion shaped intertwined projects of imperial expansion and modern nation-building. Beauty and fashion transformed political, economic, social, and cultural power that converged in the Philippines during the late nineteenth and early twentieth centuries. The Philippines became both a source and resource of beauty, though not always for Filipinos themselves. This pathbreaking book offers new ways of understanding beauty's central place in the making of imperial and nationalist power"--